One Visit Endodontic with Internal Bleaching on Tooth 12 Post Trauma: A Case Report - Pasenda Mulyadi, Reyz; Arnesti Wahab, Sofi; Cahyani, Febriastuti; Saraswati, Widya (Conservative Dentistry Journal, 2022)
Introduction: Post-traumatic non-vital teeth is one of the indications for One Visit Endodontic. Trauma to the teeth may arise from conditions that cause the teeth to become necrotic so that the teeth will look darker and experience discoloration. Clinical conditions that indicate the death of the dental pulp and teeth require endodontic treatment. This situation will cause discoloration of the teeth that occur as a result of the metamorphosis of calcified pulp. Internal whitening is a treatment that can be done after the first treatment. Purpose: To provide information about discolored teeth management after trauma which causes pulp necrosis by doing root canal treatment and internal bleaching to change tooth color. Case: A 31-year-old woman came to the RSKGMP Universitas Airlangga with a referral from the orthodontics department where her teeth were darker in color and interfered with her appearance. In the previous history, the patient had an accident and trauma 10 years ago. Case Management: The first step is access opening and a good glide path. Root canal preparation was performed using the Crown Down Pressureless technique. The obturation technique used is Single Cone. The results were good and there were no symptoms during the control. Conclusion: One visit endodontic can be a treatment option for post-traumatic non-vital teeth. Internal bleaching with Walking Bleach Technique is also proven effective in restoring the original tooth color without excessive reduction of the dental crown.